(untitled) (Jurnal Lemhannas RI, 2022)
Lake Chad Basin is facing increasing drought, desertification and climate change induced terrorism which has resulted into killing, destruction of socio-economic facilities and movement of people from the basin in search of greener pasture for their livestock down south of the country. The movement has exacerbated farmers and herders’ fight as the historical animal routes had been encroached upon by urbanization processes and farmland development. The study utilizes descriptive analysis and theory to draw inferences, recommendation for the Lake Chad basins conflict resolution. The study opines that member states had not adequately provided developmental projects for their people and the Lake Chad Basin Commission is relying heavily on international organization for funding as a result of unsatisfactory financial commitment of the member states. This paper posits while relying on the conflict resolutions theory that a rallying point or projects are needed for the conflict to end, that the Lake Chad Basin Commission members states need to capitalize on opportunities offered by climate resilient technologies such as Air to Water Technologies; technology for conversion of silt in the lake to fertilizer for agricultural development use and packaging of sun for electricity generation in the basin for member states and later for export purposes as been done in Arab desert can help to reduce the conflict in the basin area.